Mechanistic insight into reactivity and (geno)toxicity of well-characterized nanoparticles of cobalt metal and oxides. Issue 6 (3rd July 2018) - Cappellini, Francesca; Hedberg, Yolanda; McCarrick, Sarah; Hedberg, Jonas; Derr, Remco; Hendriks, Giel; Odnevall Wallinder, Inger; Karlsson, Hanna L.
Abstract: An increasing use of cobalt (Co)-based nanoparticles (NPs) in different applications and exposures at occupational settings triggers the need for toxicity assessment. Improved understanding regarding the physiochemical characteristics of Co metal NPs and different oxides in combination with assessment of toxicity and mechanisms may facilitate decisions for grouping during risk assessment. The aim of this study was to gain mechanistic insights in the correlation between NP reactivity and toxicity of three different Co-based NPs (Co, CoO, and Co3 O4 ) by using various tools for characterization, traditional toxicity assays, as well as six reporter cell lines (ToxTracker) for rapid detection of signaling pathways of relevance for carcinogenicity. The results showed cellular uptake of all NPs in lung cells and induction of DNA strand breaks and oxidative damage (comet assay) by Co and CoO NPs. In-depth studies on the ROS generation showed high reactivity of Co, lower for CoO, and no reactivity of Co3 O4 NPs. The reactivity depended on the corrosion and transformation/dissolution properties of the particles and the media highlighting the role of the surface oxide and metal speciation as also confirmed by in silico modeling. By using ToxTracker, Co NPs were shown to be highly cytotoxic and induced reporters related to oxidative stress (Nrf2 signaling) and DNA strand breaks. Similar effects were observed for CoO NPs but at higher concentrations, whereas the Co3 O4 NPs were inactive at all concentrations tested. In conclusion, our study suggests that Co and CoO NPs, but not Co3 O4, may be grouped together for risk assessment.